2019
DOI: 10.1063/1.5093421
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide/phosphate ceramics composite for electromagnetic shielding applications: Whiskers vs particles

Abstract: We report on the design of highly absorptive thermostable composite materials for microwave applications. Ceramics comprising the thermostable phosphate host and silicon carbide particles or whiskers were studied in a wide frequency range from several Hertz up to microwaves. It was demonstrated that a thin layer of ceramics placed on the back-reflector absorbs perfectly at the 30 GHz frequency. In the case of a free-standing ceramic composite layer being 1 mm thick, it provides more than 50% of absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…Although the polymer-metal composites alleviate the problems associated with corrosion and oxidation, they suffer from heavy weight and degraded efficiency at elevated temperatures. [31,32] Ceramics, [33][34][35][36][37][38][39][40] carbon fibers, [41][42][43][44][45][46][47][48] carbon black, [49,50] carbon nanotubes, [51][52][53][54][55][56][57] graphite, [58][59][60] reduced graphene oxide, [5,8,[61][62][63][64][65][66][67][68][69][70][71] graphene, [72][73][74][75][76] ferromagnetic materials, [77][78]…”
mentioning
confidence: 99%
“…Although the polymer-metal composites alleviate the problems associated with corrosion and oxidation, they suffer from heavy weight and degraded efficiency at elevated temperatures. [31,32] Ceramics, [33][34][35][36][37][38][39][40] carbon fibers, [41][42][43][44][45][46][47][48] carbon black, [49,50] carbon nanotubes, [51][52][53][54][55][56][57] graphite, [58][59][60] reduced graphene oxide, [5,8,[61][62][63][64][65][66][67][68][69][70][71] graphene, [72][73][74][75][76] ferromagnetic materials, [77][78]…”
mentioning
confidence: 99%
“…The calculations of electromagnetic shielding of thin composite plate embedded in waveguide according to equations presented in ref. [33] (please see Table 2) indicate that composites, depending from AgNPs size and concentration, are suitable for electromagnetic shielding applications. [34] T A B L E 1 Percolation threshold, fc, and corresponding critical exponents of the permittivity, g, and of the electrical conductivity, t, below and above the threshold Below room temperature, the electrical conductivity increases when the temperature decreases, and reaches a maximum around 180 K, which is close to the glass transition temperature of the pure PDMS matrix (150 K) ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The calculations of electromagnetic shielding of thin composite plate embedded in waveguide according to equations presented in ref. [ 33 ] (please see Table 2) indicate that composites, depending from AgNPs size and concentration, are suitable for electromagnetic shielding applications. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…The results are presented in Figure 4, based on calculations using the equations presented in ref. [31]. It can be concluded that layers of carbon gel with a thickness of 2 or 4 mm and a low density of about 0.2 g/cm 3 presented an absorption close to 0.5.…”
Section: Porosity Of Carbon Gelsmentioning
confidence: 88%
“…
The electromagnetic properties of various carbon gels, produced with different bulk densities, were investigated in a wide frequency range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The values of dielectric permittivity and electrical conductivity at 129 Hz were found to be very high, i.e., more than 10 5 and close to 100 S/m, respectively.
…”
mentioning
confidence: 99%